Endometriosis - novel approaches and controversies debated - W G Foster; M Leonardi (Bioscientifica, 2021)
Defined by the extrauterine growth of estrogen-dependent endometrial-like epithelial and stromal cells, endometriosis is a common gynecological and systemic inflammatory disease affecting approximately 179 million people assigned female at birth (predominately cisgender women) worldwide. Although most frequently detected in the pelvic cavity, endometriotic lesions can be found throughout the body. Three main phenotypes include endometriomas, superficial, and deep endometriosis. Lesion appearance is variable and dependent on the tissue on which it grows. Hallmark features of endometriosis include pelvic pain and infertility; however, some people with endometriosis remain asymptomatic. Endometriosis is a disease whose impact on the health care system exceeds that of caring for women with Crohn's disease, asthma, migraines, and rheumatoid arthritis (Simoens et al. 2007, 2011, 2012, Klein et al. 2014).